Mitochondria, lysosomes, and dysfunction: their meaning in neurodegeneration. Issue 3 (2nd August 2018) - Audano, Matteo; Schneider, Anja; Mitro, Nico
Abstract: In the last decades, lysosomes and mitochondria were considered distinct and physically separated organelles involved in different cellular functions. While lysosomes were thought to exclusively be the rubbish dump of the cell involved in the degradation of proteins and other cell compartments, mitochondria were considered solely involved in the oxidation of energy substrate to get ATP, together with other minor duties. Nowadays, our view of these organelles is profoundly changed since studies demonstrated that mitochondria and lysosome are mutually functional, maintaining proper cell homeostasis. Furthermore, the onset of neurodegenerative diseases (i.e., Parkinson's disease, Alzheimer's disease, lysosomal storage disorders, and amyotrophic lateral sclerosis) is tightly linked to mutations in mitochondrial and lysosomal regulators. In this context, mitochondrial dysfunction leads to lysosomal impairment and buildup of autophagy by‐products, whereas lysosomal imperfections trigger functional and morphological mitochondrial defects. Here, we provide an updated overview covering recent findings about mitochondria and lysosomal interaction in physiology and pathophysiology, focusing the attention on the molecular mechanism that control their interdependence. Abstract : Mitochondria and lysosomes are mutually functional and play a fundamental role in the maintenance of cell homeostasis. Neurodegenerative disorders such as Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis and lysosomal storage disorders originate from not fully characterized molecular mechanisms. On the other hand, recent works identified a major role of mitochondria‐lysosome network dysfunction in the onset of neurodegenerative pathologies. In this review, we describe recent advancement on the characterization of this interaction and its role in neuropathophysiology.